HASIL BELAJAR KETERAMPILAN BERMAIN BULUTANGKIS STUDI EKSPERIMEN PADA SISWA DIKLAT BULUTANGKIS FPOK-UPI - Herman Subarjah (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Effects of Learning Models on Badminton Learning Achievement. Thisstudy aims to find out the effects of the tactical approach and the conventionalapproach on the badminton learning achievement. The experiment was conductedin the Bandung Badminton Club of FPOK UPI. The results of the study were asfollows. First, in general, the skills of female badminton players using the tacticalapproach are better than those of the players using the conventional approach.Second, the skills of female players with high motor ability using the tacticalapproach are better than those of the players using the conventional approach.Third, the skills of female players with low motor ability using the tactical approachare not significantly different from those of the players using the conventionalapproach. Fourth, there is an interaction between the teaching models and motorability in relation to the female players badminton skills.Keywords : tactical approach, conventional approach, badminton learning achievement